2020
DOI: 10.1155/2020/4839876
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Processing of Image Processing Applications on CPU/GPU

Abstract: Heterogeneous systems have gained popularity due to the rapid growth in data and the need for processing this big data to extract useful information. In recent years, many healthcare applications have been developed which use machine learning algorithms to perform tasks such as image classification, object detection, image segmentation, and instance segmentation. The increasing amount of big visual data requires images to be processed efficiently. It is common that we use heterogeneous systems for such type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…for scientific applications and comparison of computational speed-up and efficiency of a GPU with a CPU time. 22,23 In 2014, A.I.S Seyed uses neural networks and decision trees (including C5.0 and CHAID). It concluded that the CHAID classifier returns the best G-mean and AUC measures for top performing predictive models ranging from 76% to 85%, and 0.812 to 0.942 units, respectively.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…for scientific applications and comparison of computational speed-up and efficiency of a GPU with a CPU time. 22,23 In 2014, A.I.S Seyed uses neural networks and decision trees (including C5.0 and CHAID). It concluded that the CHAID classifier returns the best G-mean and AUC measures for top performing predictive models ranging from 76% to 85%, and 0.812 to 0.942 units, respectively.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…(4) Since δ A and δ PD amount approximately less than or equal to 1% for N � 10 and N � 30, respectively, the correctness of the analysis performed for our SQQ model for small and medium bit rates is confirmed. is is of great importance since the accuracy of the asymptotic theory decreases noticeably for the classes of small or medium numbers of the quantization cells N. (5) e values of N at which relative error δ A increases steeply are in the very narrow range N ∈ [4,8]. (6) e largest relative error δ A � 3.68% occurs for the smallest observed number of levels N � 4.…”
Section: Numerical Results and Analysismentioning
confidence: 99%
“…A promising deployment of QNN in many contemporary approaches and artificial intelligence applications reduces the overall computational and memory cost [5]. As shown in [8], this is of great importance since the amount of data to be processed constantly grows so that more powerful hardware (CPU/GPU) is required. Moreover, the QNN approach addressed in [5] is particularly beneficial for implementing in models with the extreme memory requirements, such as mobile devices and edge devices.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the small workload has a total of ≈ 800 jobs (a moderately loaded system), and the large workload a total of ≈ 1400 jobs (a congested system). Both workloads are based on [7], which details the amount of time required to perform edge detection on 1980 × 1020 images using a core i5 processor (hence the MB/s units for C i and K j ). We assume the time required scales linearly with the number of images being processed.…”
Section: Results For Pipeline Processingmentioning
confidence: 99%